Efek Penambahan Vitamin E dalam Pengencer Glukosa Fosfat terhadap Daya Tahan Hidup Spermatozoa Domba pada Suhu 5 °C - Widjaya, Nilawati (Universitas Sebelas Maret (UNS), 2011)
The purpose of this study was to know the effect of vitamin E addition in glucose phosphate diluent on the survival of sheep spermatozoa at 5 °C. The xperiment used 3 rams. The design used was Completely Randomized Design (CRD) with 5 treatments and 4 replicates, each replicate with 3 ejaculate cement of sheep. The treatments were the dose of Vitamin E with E0 = 0 μg/ml, E1 = 1 μg/ml, E2 = 4 μg/ml, E3 = 7 μg/ml, and E4 = 10 μg/ml. Variables measured were motility, live spermatozoa and plasma membrane integrity. Data were analyzed by using analysis of variance according to Steel and Torrie (1981). The result showed that treatment of vitamin E with a dose of 1 μg/ml - 10 μg/ml l had no significant effect on motility, percentage live spermatozoa and membrane integrity of sheep spermatozoa on day two (P> 0.05).